2001
DOI: 10.1021/om000670d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Substitution of Weakly Coordinating Nitrate by Chloride in (η5-Cp)Ru(CO)(ER3)ONO2 (ER3 = AsPh3, PPh3, P(p-anisyl)3, PPh2(o-anisyl), P(OPh)3) in Dichloromethane

Abstract: The d 6 complexes of formula (η 5 -Cp)Ru(CO)(ER 3 )ONO 2 , where ER 3 ) AsPh 3 , PPh 3 , P(panisyl) 3 , PPh 2 (o-anisyl), and P(OPh) 3 , were prepared by reaction of their chloro analogues with AgNO 3 in CH 2 Cl 2 . They underwent moderately slow substitution of the relatively weakly coordinating nitrate by chloride in dry CH 2 Cl 2 in the presence of excess [N(PPh 3 ) 2 + ]Cl -. A kinetics study showed the reaction to be first order in nitrato complex and independent of chloride salt concentration under pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…All the complexes display a strong band in the region 1942e1949 cm À1 which is attributed due to the terminally coordinated carbonyl group and is observed at slightly higher frequency than in the precursor complexes. In addition, other characteristic bands due to ruthenium bound PPh 3 /AsPh 3 in the region 1436e1447 cm À1 are also present in the spectra of all the complexes [36]. The IR spectra of all the complexes therefore confirms the coordination mode of the benzoylhydrazone ligand to ruthenium(II) ion via the phenolate oxygen, the azomethine nitrogen and the imidolate oxygen and indicates the presence of PPh 3 /AsPh 3 groups.…”
Section: Spectral Characterizationmentioning
confidence: 56%
“…All the complexes display a strong band in the region 1942e1949 cm À1 which is attributed due to the terminally coordinated carbonyl group and is observed at slightly higher frequency than in the precursor complexes. In addition, other characteristic bands due to ruthenium bound PPh 3 /AsPh 3 in the region 1436e1447 cm À1 are also present in the spectra of all the complexes [36]. The IR spectra of all the complexes therefore confirms the coordination mode of the benzoylhydrazone ligand to ruthenium(II) ion via the phenolate oxygen, the azomethine nitrogen and the imidolate oxygen and indicates the presence of PPh 3 /AsPh 3 groups.…”
Section: Spectral Characterizationmentioning
confidence: 56%
“…1 H (400 MHz) and 77 Se{ 1 H} NMR (76 MHz) spectra were recorded on a JEOL ECZ 400 spectrometer at ambient temperature. 13 C{ 1 H} NMR (126 MHz) spectra were recorded on aJ EOL JNM-ECA500 spectrometer at ambient temperature. 125 Te { 1 H} NMR spectra were recorded on aJ EOL JNM-ECS300 spectrometer at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…125 Te { 1 H} NMR spectra were recorded on aJ EOL JNM-ECS300 spectrometer at ambient temperature. Chemical shifts d are reported in ppm and are referenced to the residual 1 Ha nd 13 Cs ignals of CDCl 3 as the internal standard ( 1 HNMR: d = 7.24; 13 CNMR: d = 77.0 ppm) or to the 77 Se signal of PhSeSePh (d = 459.0 relative to MeSeMe at d = 0ppm) [28] and to the 125 Te signal of PhTeTePh (d = 422.0 relative to MeTeMe at d = 0ppm) [29] as external standards. IR spectra were recorded on a JASCO FT/IR-4600 spectrometer with ad iamond-attenuated total reflectance (ATR) unit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, multinuclear NMR spectroscopic studies revealed that [(h 5 -C 5 H 5 )Ru(CO){PPh 2 (C 6 H 4 X-2)}] + (X = Cl, Br), formed by silver(I)-mediated chloride abstraction from [(h 5 -C 5 H 5 )RuCl(CO){PPh 2 (C 6 H 4 X-2)}], possessed an intramolecular RuÁ Á ÁX interaction, whereas no RuÁ Á ÁF interaction was observed on chloride abstraction from [(h 5 - [124]. These observations were supported by calculations that revealed that there is no stabilization gained by a RuÁ Á ÁF interaction in the cation [(h 5 -C 5 H 5 )Ru(CO){PPh 2 (C 6 H 4 F-2)}] + , although considerable stabilization arose for the chloride and bromide analogues [125]. Similarly IrÁ Á ÁCl and IrÁ Á ÁBr interactions, but not an IrÁ Á ÁF interaction, are found in [(COD)Ir{PPh 2 (C 6 H 4 X-2)}] + (COD = h 2 ,h 02 -cycloocta-1,5-diene) [126].…”
Section: Má á áF-c Interactionsmentioning
confidence: 69%